2019
DOI: 10.1002/jmv.25547
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA GAS5 does not regulate HBV replication

Abstract: Hepatitis B virus (HBV) infection remains a severe health burden worldwide.Emerging long noncoding RNAs (lncRNAs) are hijacked to enhance virus replication or employed by the host to stimulate immune responses to clear the virus. LncRNA growth arrest-specific transcript 5 (GAS5) can regulate RNA virus by suppressing the replication of both hepatitis C virus and human immunodeficiency virus. In this study, we explored the changes of HBV replication by overexpressing or knocking down GAS5 in HepAD38 cell and Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In our study, GAS5 expression was significantly down-regulated in CHBV patients compared to controls. Our results were consistent with Feng et al, who reported down-regulation of GAS5 in patients with CHBV when compared to healthy controls 18 . Furthermore, in a study that identified the lncRNAs expression patterns in CHBV, GAS5 was down-regulated as compared to the healthy controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, GAS5 expression was significantly down-regulated in CHBV patients compared to controls. Our results were consistent with Feng et al, who reported down-regulation of GAS5 in patients with CHBV when compared to healthy controls 18 . Furthermore, in a study that identified the lncRNAs expression patterns in CHBV, GAS5 was down-regulated as compared to the healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting that both IFN‐α and IFN‐λ levels remained low during HCV infection after GAS5 overexpression, revealing the ability of GAS5 to inhibit innate immune responses after viral infection 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm the role of LINC01431 against HBV in vivo, LINC01431‐PT3EF1 α plasmid was injected into HBV carrier mice prepared by pAAV‐HBV1.2 hydrodynamic injection (HDI), the nucleotide analogues Entecavir (ETV) was selected as a positive control, and lncRNA GAS5, which showed no role in HBV replication, [ 26 ] as a negative control (Figure 2D and Figure S2D, Supporting Information). As expected, compared with GAS5, LINC01431 overexpression significantly reduced the serum levels of HBsAg and HBV DNA, as well as hepatic HBcAg expression, while ETV treatment significantly decreased the levels of serum HBV‐DNA but not HBsAg (Figure 2E,F and Figure S2E, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The rate of HCV infection prevalence varies between 0.1% -12% and is country dependent 5 . Around 350 million people were living with chronic HBV infection (8)(9)(10) and about 160 million people with HCV 4 and other declared 170 million people with CHCV infection in 2002 worldwide 8 . In 2009 figure reached 200 million which made 3.3% of the global population 4 .…”
Section: Introductionmentioning
confidence: 99%